LUTETIACADER, A PUZZLING NEW GENUS OF CANTACADERID LACE BUGS (HETEROPTERA: TINGIDAE) FROM THE MIDDLE EOCENE MESSEL MAAR, GERMANY - Wappler T. (My University, 2006)
A new genus of cantacaderid lace bugs, Lutetiacader gen. et sp. nov., is described from the lower Middle Eocene of Messel Quarry, Germany. It clearly belongs to the cantacaderid lineage of Tingidae, and is the second known fossil genus of the tribe Cantacaderini (after Paleocader Froeschner). It appears to be most similar to extant species of the genera Nectocader Drake (Brazil) and Teratocader Drake (Malay Peninsula). Lutetiacader occupies a central position with respect to the geographical gap between the ranges of these two extant genera. Its biogeographical significance is discussed.
Keywords: Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен